Mechanistic Details of the Spontaneous Intercalation of Li Metal into Graphite Electrodes. Issue 14 (18th November 2020) - Hogrefe, Christin; Hein, Simon; Waldmann, Thomas; Danner, Timo; Richter, Karsten; Latz, Arnulf; Wohlfahrt-Mehrens, Margret
Abstract : The mechanism of the spontaneous intercalation of Li metal into graphite electrodes is highly relevant for aging mechanisms and pre-lithiation of Li-ion cells. In the present work, we introduce a method to investigate this mechanism via measuring the open-circuit-potential (OCP). Experiments without electrolyte, with organic solutions without and with LiPF6 reveal details on the reaction mechanism at 29 °C. The electrodes are investigated by Raman spectroscopy and glow-discharge optical emission spectroscopy (GD-OES) depth profiling to reveal the spatial distribution of the lithiated phases. The analytical information is enriched by simulations with the Battery and Electrochemistry Simulation Tool (BEST). The combination of tools gives interesting insights into the behavior of negative electrodes regarding re-intercalation of deposited Li into graphite and its kinetics, development of inhomogeneities during aging, as well as pre-lithiation and post-mortem analysis methodology.